Использование минерального сырья на позднепалеолитическом поселении Анетовка 2 - Главенчук, А.В. (Материалы по археологии Северного Причерноморья, 2015)
The artifacts derived by contemporary archaeologists from culture layers of dwelling places of Late Palaeolithic human population are presented predominantly by minerals and mineral wares. Unlike organic materials, such items are less liable to destruction through time. The Late Palaeolithic site of Anetovka 2 (Domanyovka district of Nikolayev region, Ukraine) gives the evidence of wide and intensive usage of mineral raw-stuff. Flint was the basic material for tool manufacture at the site; besides the excavation materials from cultural layer include artifacts and manuports made of various kinds of stones (large and small sized) and mineral clays.